2010
DOI: 10.1002/ange.200906670
|View full text |Cite
|
Sign up to set email alerts
|

Wechselwirkungen zwischen amyloidogenen Proteinen und Membranen: Modellsysteme liefern mechanistische Einblicke

Abstract: Die Toxizität amyloidbildender Proteine ist mit ihrer Wechselwirkung mit Membranen korreliert. Bemerkenswerterweise führen Bindungsereignisse zwischen amyloidogenen Proteinen und Membranen beiderseits zu Strukturstörungen, die mit Toxizität assoziiert sind. Membranoberflächen vermitteln die Umwandlung amyloidbildender Proteine in toxische Aggregate, amyloidbildende Proteine wiederum beeinträchtigen die strukturelle Integrität der Zellmembran. Neuere Untersuchungen an künstlichen Modellmembranen haben eine beme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 226 publications
(464 reference statements)
1
11
0
Order By: Relevance
“…[8a] This result indicates that the progress of Ab fibrillation follows a typical nucleation-growth mode that consists of three stages: lag phase, elongation phase, and stationary phase. [15] The saturation of the ThT FI after approximately 90 h indicates that all of the Ab end up in the form of fibrils (also see Figure 2 c). Upon the introduction of MSPMs, the lag phase extended and the FI at saturation decreased, indicating that the MSPM-based chaperone can effectively suppress the Ab fibrillation process.…”
Section: Methodsmentioning
confidence: 90%
“…[8a] This result indicates that the progress of Ab fibrillation follows a typical nucleation-growth mode that consists of three stages: lag phase, elongation phase, and stationary phase. [15] The saturation of the ThT FI after approximately 90 h indicates that all of the Ab end up in the form of fibrils (also see Figure 2 c). Upon the introduction of MSPMs, the lag phase extended and the FI at saturation decreased, indicating that the MSPM-based chaperone can effectively suppress the Ab fibrillation process.…”
Section: Methodsmentioning
confidence: 90%
“…[9][10][11] Several studies have shown that lipid-peptide interactions can play a crucial role in amyloid formation of both IAPP and Ab, [1,3,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] and the enhancement of fibrillation in the presence of membranes is believed to be causatively linked to the cellular damage caused by Ab or IAPP assemblies. [25,26,28] Here, the interaction of IAPP and Ab with a complex heterogeneous (raft-like) model biomembrane system comprising 15 % DOPC, 10 % DOPG, 40 % DPPC, 10 % DPPG, and 25 % cholesterol has been studied. This lipid system allows for addressing effects of lateral heterogeneity (i.e., coexisting liquid-disordered and liquid-ordered domains) as well as charge effects upon peptide-membrane interactions.…”
mentioning
confidence: 99%
“…[1] Biological membranes supported on substrates are widely used to mimic the dynamics and structural features of cell membranes, [2,3] and proteins embedded in them could carry out a wide range of physiological and biochemical processes. [1] Biological membranes supported on substrates are widely used to mimic the dynamics and structural features of cell membranes, [2,3] and proteins embedded in them could carry out a wide range of physiological and biochemical processes.…”
mentioning
confidence: 99%